2008
DOI: 10.1063/1.2937409
|View full text |Cite
|
Sign up to set email alerts
|

Integration of thin layers of single-crystalline InP with flexible substrates

Abstract: Transfer of thin semiconductor layers onto flexible substrates using a combination of ion cutting, adhesive bonding, and laser ablation was investigated. An ∼1.3μm thick InP layer was first transferred onto sapphire using adhesive bonding and hydrogen-induced layer exfoliation at ∼180°C. The resulting structure was then adhesively bonded onto flexible polyethylene naphthalate substrate, followed by UV laser ablation of the first adhesive to separate the initial bond. Additional transfer steps were inserted int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
17
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…3 Recent work with ion-cutting and adhesive bonding has shown that a prefabricated device layer transfer, i.e., the transfer of a layer with a device already fabricated on it, may be feasible in a double-flip transfer process, allowing for the integration of high-speed, InP-based devices with materials such as flexible substrates. 4 Such a process would not require any further device-fabrication processes ͑such as epitaxial regrowth͒ after transfer. However, to exfoliate an implanted InP layer using the ion-cut method, it is generally necessary to implant hydrogen ions at a high dosage of several times 10 16 /cm 2 into the semiconductor donor.…”
mentioning
confidence: 99%
“…3 Recent work with ion-cutting and adhesive bonding has shown that a prefabricated device layer transfer, i.e., the transfer of a layer with a device already fabricated on it, may be feasible in a double-flip transfer process, allowing for the integration of high-speed, InP-based devices with materials such as flexible substrates. 4 Such a process would not require any further device-fabrication processes ͑such as epitaxial regrowth͒ after transfer. However, to exfoliate an implanted InP layer using the ion-cut method, it is generally necessary to implant hydrogen ions at a high dosage of several times 10 16 /cm 2 into the semiconductor donor.…”
mentioning
confidence: 99%
“…7 A major drawback to the process is that the implantation damage leads to electrically active defects which are difficult to eliminate. Bulk characteristics cannot be fully restored even after annealing to 600°C.…”
mentioning
confidence: 99%
“…SU-8 is a suitable adhesive for ion-cutting provided temperatures are kept below 200°C. 7 Sapphire was chosen because of its ultraviolet ͑UV͒ transparency. Bonding was done following SU-8 spincoat and solvent evaporation at 150°C.…”
mentioning
confidence: 99%
“…Therefore, we must use III-V compound semiconductors for light sources, and various studies have recently been conducted using III-V semiconductor lasers on Si substrates. [3][4][5][6][7][8] Semiconductor quantum dot (QD) lasers, which have various advantages including low threshold current and high temperature stability, utilize the discrete electrical density of states in QDs (Ref. 9) and are therefore suitable for high-density integration.…”
mentioning
confidence: 99%